How applicable is the USDA Thrifty Food Plan for the average college student? - Alsaati, Malak (My University, 2025)
Background: Eating balanced meals and meeting the dietary guidelines has become a major problem among college students, significantly affecting their academic performance and overall health. The USDA Thrifty Food Plan (TFP), designed to help consumers obtain the necessary nutrient needs within a budget, may also be adopted by college students. Financial limitations and time management are some barriers that prevent college students from meeting dietary recommendations and the guidelines recommended by TFP. Objective: This study aims to determine the applicability of the USDA Thrifty Food Plan to college students by assessing how well college students are meeting recommendations for food spending, dietary intake, and food security according to the TFP. In addition to examining whether food insecurity affects nutritional adequacy within budgetary limits. Methods: A cross-sectional study of (n=171) college students at a midwestern university participated in an online survey. The survey collected data on demographic information, grocery habits, food security status, and dietary intake. Students were asked to provide information about their knowledge of the USDA Thrifty Food Plan and if they follow a budget-friendly food plan. Descriptive analysis was used to calculate students' monthly food spending, percentage of meeting the dietary guidelines, and level of food insecurity against the Thrifty Food Plan allowance. Results: Most students (96%) never attempted to follow the USDA Thrifty Food Plan. The Monthly food spending for students who didn’t purchase a meal plan ranged from $139 - $240, which is below the TFP recommended budget of $241.40-$309.90. Food insecurity affected a small portion of students who reported experiencing occasional food insecurity and stating they could not afford nutritious food regularly. In addition, only a few (6.4%) of respondents met MyPlate dietary recommendations for the five food groups. The gap between student food spending and the TFP allowance, and food insecurity, created barriers for students to achieve nutritional balance.
Keywords: USDA food plans; College students; Dietary habits; Food insecurity